(untitled) (Indonesian Journal of Agrarian Law, 2026)
Although Indonesia’s land registration system theoretically adopts a negative publication system with positive elements, in practice it still creates vulnerabilities that lead to legal uncertainty for land rights holders. This is reflected in recurring cases of double certificates, overlapping ownership claims, and weak integration of national land data, which often trigger prolonged disputes and affect economic stability. This empirical study examines the gap between administrative recognition issued by the government and its evidentiary strength before judges who apply the principle of judicial freedom in evaluating evidence. The research aims to assess the effectiveness of electronic land certificates in achieving substantive legal certainty. The study was conducted through field research methods, including in-depth interviews with civil judges, analysis of Supreme Court Decision Number 170 K/Pdt/2017, and examination of jurisprudence related to electronic documents. The findings indicate that electronic certificates provide technical advantages such as data encryption, audit trails, and national data synchronization. This innovation still operates within the framework of the negative publication system, which was not designed to accommodate a shift toward digital proof mechanisms. Furthermore, there has not yet been any court ruling that specifically regulates the evidentiary status of electronic certificates in land disputes, creating a potential legal vacuum. Although Supreme Court Decision Number 170 K/Pdt/2017 concerns a conventional certificate dispute, it establishes a precedent that courts prioritize material truth and the principle of prior tempore potior iure over administrative legitimacy.